Ultrathin Zincophilic Interphase Regulated Electric Double Layer Enabling Highly Stable Aqueous Zinc-Ion Batteries - Chen, Yimei; Deng, Zhiping; Sun, Yongxiang; Zhang, Yue; Zhang, Hao; Li, Ge; Zeng, Hongbo; Wang, Xiaolei (Nano-Micro Letters, 2024)
The practical application of aqueous zinc-ion batteries for large-grid scale systems is still hindered by uncontrolled zinc dendrite and side reactions. Regulating the electrical double layer via the electrode/electrolyte interface layer is an effective strategy to improve the stability of Zn anodes. Herein, we report an ultrathin zincophilic ZnS layer as a model regulator. At a given cycling current, the cell with Zn@ZnS electrode displays a lower potential drop over the Helmholtz layer (stern layer) and a suppressed diffuse layer, indicating the regulated charge distribution and decreased electric double layer repulsion force. Boosted zinc adsorption sites are also expected as proved by the enhanced electric double-layer capacitance. Consequently, the symmetric cell with the ZnS protection layer can stably cycle for around 3,000 h at 1 mA cm−2 with a lower overpotential of 25 mV. When coupled with an I2/AC cathode, the cell demonstrates a high rate performance of 160 mAh g−1 at 0.1 A g−1 and long cycling stability of over 10,000 cycles at 10 A g−1. The Zn||MnO2 also sustains both high capacity and long cycling stability of 130 mAh g−1 after 1,200 cycles at 0.5 A g−1. Highlights: 1 Electric double-layer regulation enabled by an ultrathin multifunctional solid electrolyte interphase layer with zincophilicity and rapid transport kinetics. 2 Lowered potential drop over the Helmholtz layer and suppressed diffuse layer. 3 Inhibited side reactions and uniform zinc deposition.